Rekonstruksi Pemikiran Islam Muhammad Iqbal - AGUS ANWAR PAHUTAR (Yayasan Baitul Hikmah al-Zain, 2024)
This article examines the Reconstruction of Islamic Thought of Muhammad Iqbal, which is his intellectual effort to reformulate and modernize the understanding of Islam amidst the challenges of the modern era. By placing an in-depth analysis of various religious aspects in the context of the social, political, and intellectual upheavals of the early 20th century, Iqbal offers an innovative perspective that aims to harmonize Islamic traditions with modern scientific and philosophical principles. This paper explores how Iqbal challenges the stagnation of religious thought by emphasizing the importance of ijtihad (independent interpretation), integrating reason and revelation, and re-understanding the concept of 'khudi' (ego or self) to achieve full human potential. By elaborating on these principles, Iqbal tried to generate intellectual and religious enthusiasm that could encourage Muslims to face modernity in a more effective and creative way. This paper also discusses the relevance of Iqbal's ideas in the current global context and their potential to influence contemporary discussions regarding identity, freedom, and intercultural harmony.